1990
DOI: 10.1016/0020-7292(90)90158-h
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian management at the time of radical hysterectomy for cancer of the cervix

Abstract: GYNECOL ONCOL 1989,35/3 (349-351) Ovarian management at the time of radical hysterectomy for cervical cancer was reviewed retrospectively over a 7-year period. All patients had early-stage cancer except three who had stage IIB disease. Approximately 80% of patients had squamous cancer and 20% adenocarcinoma or adenosquamous carcinoma. The mean age was 44, and 24% of patients were 35 or younger. Ninety-nine patients had their ovaries removed. None of the ovaries contained metastatic disease including 22 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Of the 36 patients who did not receive adjuvant pelvic radiotherapy, 2 (5.5%) became postmenopausal, whereas 5 (28%) of the patients who received adjuvant pelvic radiotherapy became postmenopausal. This is consistent with several other studies which report a postmenopausal rate in irradiated patients with LOT of 0% to 30% (6–9,11) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Of the 36 patients who did not receive adjuvant pelvic radiotherapy, 2 (5.5%) became postmenopausal, whereas 5 (28%) of the patients who received adjuvant pelvic radiotherapy became postmenopausal. This is consistent with several other studies which report a postmenopausal rate in irradiated patients with LOT of 0% to 30% (6–9,11) .…”
Section: Discussionsupporting
confidence: 93%
“…Six other studies have also examined the sequelae of LOT in irradiated cervical cancer patients (7–12) . Five studies reported no ovarian cyst formation (8–12) .…”
mentioning
confidence: 99%
“…Regarding the association of tumor histology and ovarian metastasis, Tabata et al (12) noted that ovarian metastasis is frequently found in patients with adenocarcinoma. Other investigators have reported that the rate of ovarian metastasis was not related with histologic type (11,13,14). The risk of ovarian metastasis in transposed ovary increases in patients with a bulky tumor (12,13).…”
Section: Discussionmentioning
confidence: 94%
“…The effectiveness of lateral ovarian transposition for ovarian preservation after adjuvant radiation has been studied. In three studies, the rate of ovarian failure after adjuvant radiation in patients after lateral ovarian transposition varied widely from 17.0%-88.6% (9,14,15). Another study reported that 57% of patients experienced ovarian failure after transposition of ovary more than 3 cm above the umbilical line (17).…”
Section: Discussionmentioning
confidence: 94%
“…Brown et al 11 have reported that ovarian metastases are rare in stage I adenocarcinoma of the cervix, and that only one of 25 stage I adenocarcinoma patients (4.0%) had had a microscopic ovarian metastasis. Owens et al 12 have argued that in stage I adenocarcinoma patients without lymph node metastasis, ovaries can be left. Ovarian metastasis has been observed to occur more frequently in patients with adenocarcinoma than in patients with squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%